The biological applications of IPN hydrogels - Maria I. León-Campos; Juan J. Mendoza; Hilda Aguayo-Morales; Luis E. Cobos-Puc; Denis A. Cabrera-Munguía; Jesús A. Claudio-Rizo (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Interpenetrating polymer network (IPN) hydrogels are an adaptable category of materials, exhibiting remarkable promise for various biological applications due to their distinctive structural and functional attributes. This review delves into the synthesis of IPN hydrogels through both physical and chemical methodologies, elucidating how these techniques allow for precise tailoring of mechanical properties, swelling behaviour, and biocompatibility. Experimental approach: We conducted an extensive literature review by searching well-established online research databases for articles published since 2009 to gather comprehensive data on IPN hydrogels. Key results: Our review highlights several critical applications of IPN hydrogels in the biomedical field; i) Tissue engineering: IPN hydrogels are evaluated for their capacity to emulate the extracellular matrix, making them excellent scaffolds for tissue engineering; ii) Controlled drug release: The ability of IPN hydrogels to modulate drug release rates and protect bioactive molecules is explored. Their structure enables sustained and targeted delivery of therapeutic agents, enhancing treatment efficacy; iii) 3D bioprinting: The use of IPN hydrogels as bioinks for 3D bioprinting is assessed, demonstrating their capability to construct intricate, biomimetic structures with high precision; and iv) Regenerative medicine: the development of biomimetic IPN hydrogels for regenerative medicine, emphasizing their potential to closely replicate natural biological environments, thereby promoting effective tissue repair and regeneration. Conclusion: IPN hydrogels emerge as a versatile and multifaceted platform with significant implications for advancing biomedical science and clinical therapies. Their diverse applications highlight their potential to revolutionize current biomedical practices and contribute to the development of innovative therapeutic solutions.